Comparative seismic behavior the retrofit of 60year old hospital between CFRP materials and concrete walls by nonlinear static analysis - Criales, Xiomara (2022)
The Casimiro Ulloa Hospital is a confined masonry structure more than 60 years old that does not satisfy the requirements of the Peruvian seismic code E.030 and it is located at high seismic zone. Therefore, this hospital is susceptible to collapse and becomes an essential deficient structure. Therefore, the present study is based on a comparative analysis between reinforced concrete wall and CFRP sheets through the nonlinear Push Over method in order to obtain which is the best reinforcement in structural capacity. The reinforcement with eight L-shaped concrete walls of 15 cm thick located at the corners of the structure, increased the strength of the hospital by 115% in longitudinal direction (Axis X) and 108% in transversal direction (Axis Y), and also increased the ductility by 3% and 117% in the directions respectively. The other reinforcement was carried out with CFRP sheets and anchors. The sheets were designed with a width of 9 inches and were placed in an X-shape in the masonry load-bearing walls and the anchors were implemented in the corners of the laminate walls in order to ensure adequate load transfer between the sheets and the surface. This reinforcement increased the strength of the structure by 345% in axis X and 150% in axis Y and increased the ductility by 59% in longitudinal direction and 331% in transversal direction.